Analysis of differential item functioning on computer studies multiple choice questions in WAEC senior secondary school certificate examinations (2018)
The study analysed the differential item functioning of computer studies multiple choice items by WAEC. The study adopted descriptive research design of survey type. Stratified random sampling was used for the and the sample size was 150 participants from public and private secondary schools in Ogun state and the sample contain both male and female students from rural and urban areas of the state. The study answered three research questions. The study used WAEC pass questions to establish items discrimination and items difficulties. The finding showed that the location, gender and school type affected students' performance. Based on this, the researcher recommends that the examination bodies should ensures that the items are not too difficult for the testees; moderate the difficulty level of their items and that government should level the differences between private and public school